Adverse drug reaction patterns of anti-retroviral drugs: A study in a tertiary care teaching Institute of north east India - ZOSANGPUII, CHRISTINA; DATTA, SWAGATA; GUNINDRO, NGANGOM; MEENA, DN; NAMEIRAKPAM, SURJIT SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The use of antiretroviral drugs is associated with significant safety concerns but there is still insufficient data about the toxicity profile of ART drugs especially in developing countries. Hence, this study was done to describe the severity and pattern of different types of adverse drug reactions that occurs with antiretroviral therapy. Method: A retrospective cross-sectional study was done at Pharmacovigilance centre RIMS utilizing data from January 2016 till December 2019. Result: A total of 190 cases reported during the study period were included in this study. Incidence was higher in females (109) as compared to males (81). The most common regimen responsible was TLE (69.5%) followed by ZLN (16.3%). Involvement of dermatological system (27.4%) was most common. The most common ADR associated with TLE was skin rash (28.3%) which was less severe as compared to the most common ADR associated with ZLN, which was anaemia (40.6%). On evaluation of WHO-UMC causality of ADRs, majority were found to be possible (78.2%). Conclusion: TLE regimen requires special focus as it was the most common regimen causing ADR but patients on ZLN regimen need to be closely monitored as they were found to cause more serious ADRs. A more active pharmacovigilance is needed for better understanding of toxicities related to ART. Key words: Adverse drug reactions, Pharmacovigilance, WHO-UMC criteria, Anti-retroviral therapy.